Markers of immune activation: novel biomarkers to predict the early-warning indicator of patients with papillary thyroid carcinoma - Hongsheng Lu; Lihong Zhang; Yuechu Dai; Yanyun Ruan; Xuequan Cao; Xiaobo Cai; Sihan Ruan; Qi Chen (BMC, 2020)
Abstract Background Papillary thyroid carcinoma (PTC) is an indolent tumor that is exploding with increasing thyroid nodules (TN). Environmental carcinogens, lifestyle changes increased the incidence of thyroid carcinoma. With the development of B-ultrasound imaging, more and more thyroid cancer has been found. There has been a debate about whether thyroid cancer is overtreated. Methods The expression of T cell subsets and plasma cytokines in 191 patients, including 79 patients with PTC (PTC group), 58 patients with thyroid nodules (TN group) and 54 healthy individuals (HP group) were analyzed by flow cytometry. Results High levels of natural killer cells (NK) were detected in PTC and TN groups than in HP group. High activities of CD8+HLA-DR+ and CD8+CD38+ showed a gradual upward trend from HP group to PTC group. The rise in the levels of TNF-α in PTC patients' was evident when compared with HP group. CD8+CD38+ showed a significant correlation with lymph node metastasis. CD8+CD38+ co-expression was higher in Nx stage than N0 stage, while the proportion of IL-10 was dramatically decreased in the Nx stage. Conclusions These results indicated that CD8+CD38+ might act as a biomarker of PTC lymph node metastasis. The combination of CD8+HLA-DR+, CD8+CD38+ and TNF-α can be used as useful biomarkers for the early-warning indicator of PTC.